Emotionally Based School Avoidance in the Aftermath of the COVID-19 Pandemic: Neurodiversity, Agency and Belonging in School - Lorna G. Hamilton (MDPI AG, 2024)
Lockdowns at the peak of the COVID-19 pandemic led to extended school closures globally, and in many countries school attendance has not recovered to pre-pandemic levels. In England, education leaders have expressed concern both about increased anxiety among pupils and chronic absenteeism post-pandemic, against a backdrop of over a decade of increasing mental health need among children and young people. This article presents a narrative review with the aims of (a) conceptualising emotionally based school avoidance (EBSA), and (b) identifying strategies for supporting children and young people experiencing psychological barriers to attending school. The underlying reasons for school being experienced as a hostile environment by a minority of pupils are explored, with research findings specifically relating to the school experiences of neurodivergent pupils in mainstream settings included as an illustrative example. The psychological constructs of belongingness and agency are discussed as potential mechanisms of change. Finally, psychologically informed strategies to address EBSA are reviewed, drawing on the framework of multiple systems of support. To reduce absenteeism in pupils experiencing EBSA, and thus avoid exacerbating educational inequalities in disadvantaged groups, it is essential to understand psychological barriers to school attendance and to work collaboratively and compassionately with pupils and families towards solutions.